The effect of different wavelengths of light during incubation on the development of rhythmic pineal melatonin biosynthesis in chick embryos. (7th January 2019) - Drozdova, A.; Okuliarova, M.; Zeman, M.
Abstract : Rhythmic pineal melatonin biosynthesis develops in chick embryos incubated under a light (L)-dark (D) cycle of polychromatic white light. The spectral sensitivity of the embryonic pineal gland is not known and was investigated in this study. Broiler breeder eggs (Ross 308, n =450) were incubated under white, red, green or blue light under the 12L : 12D cycle. Melatonin was measured in extracts of pineal glands by radioimmunoassay. The daily rhythm of pineal melatonin levels in 20-day-old chick embryos was confirmed during the final stages of embryonic life under all four wavelengths of light with expected higher concentrations during dark- than light-times. The highest pineal melatonin levels were determined in chick embryos incubated under red and white light and lower levels under green light. The incubation under blue light resulted in the lowest melatonin biosynthesis. Pineal melatonin concentrations increased substantially on post-hatching day two compared with pre-hatching levels and we did not find differences between birds incubated and kept in either white or green light. Our results demonstrate a selective sensitivity of the chick embryo pineal gland to different wavelengths of light. Rhythmic melatonin production is suggested as a possible mechanism, which transfers information about the quality of ambient light to the developing avian embryo.